Машины и оборудование для устройства оснований и фундаментов - Смородинов М. И. Михаил Ильич; Ерофеев Л. В. Лев Викторович; Федоров Б. С. Борис Сергеевич; Вязовикин В. Н. (Москва, Машиностроение, 1985)
Авт. указаны на обороте тит. л.